The Late Pleistocene - Holocene meandering lower Garonne River, southwest France: Architecture of the valley fill and chronology, comparison with other European rivers - Pascal Bertran; Eric Andrieux; Sophie Leleu; Zoe Sicard-Delage; Benjamin Fores; Rachid Ouchaou; Pierre Weill; Jean-Yves Reynaud (Geomorphology, 2025)

Incision and rock uplift along the Lower Seine River since Marine Isotope Stage 8 - Diana Chourio‐Camacho; Jean‐Louis Grimaud; Hélène Tissoux; Paul Bessin; Pierre Voinchet; Emmanuel Vartanian; Mark Noble; Pascal Bertran (Journal of Quaternary Science, 2024)
The study of alluvial terraces helps in reconstructing the past geometries of rivers and makes it possible to assess the rate and pattern of fluvial incision and bedrock uplift. The fluctuations of river base levels are particularly variable and complex during the Late Quaternary in the lower course of rivers due to the interplay of responses to sea‐level fluctuations, tectonics and glacio‐isostasy. In this paper, the geometry and chronology of Manoir Brésil, an outcrop of alluvial terraces of the Lower Seine River, northern France, are investigated through a multidisciplinary study. Fluvial incision during MIS 8 in the Lower Seine in relation to sea‐level drop is recorded by an erosional surface cut into the chalk bedrock. This surface is covered by MIS 7 tidal deposits and then by younger, mostly periglacial colluvium (head). Manoir Brésil is therefore considered to be a chronological equivalent of the nearby, well‐studied Tourville‐la‐Rivière outcrop. The deposits are affected by post‐MIS 7 cryoturbation processes. Based on the local elevation of MIS 7 tidal deposits and erosional surfaces at Manoir Brésil, a minimum bedrock uplift rate of 25–40 m/Ma and an erosion rate of 125 m/Ma during glacial periods can be proposed. A regional correlation of the MIS 8 erosional surface is increasingly deformed by uplift towards the North, making it difficult to correlate the fluvial deposits along the Seine without precise chronological control. We interpret this regional tilt as the result of isostasy rebound after glaciations, consistent with the distribution of the elevations of MIS 5e and MIS 7 marine deposits along the English Channel.

Last Interglacial–Glacial sequence of palaeosols and calcareous slope deposits at Verteuil (Charente, southwest France) - Jules Puyrigaud; Pascal Bertran; Brice Lebrun; Christelle Lahaye; Guillaume Guerin; Nicole Limondin‐Lozouet (Journal of Quaternary Science, 2023)
The 12 m thick sequence of calcareous slope deposits and palaeosols exposed in a quarry at Verteuil (southwest France) has been studied and dated by optically stimulated luminescence. Emphasis was given to the identification and characterisation of palaeosols through geochemistry and micromorphology. The main clastic units, separated by major unconformities, were dated to MIS 6, MIS 5–4 and MIS 3–2. Stratified deposits (‘grèzes litées’), consisting of alternating diamictic and matrix‐free clastic beds and attributed to stacked stone‐banked solifluction lobes, developed mainly after ca . 40 ka, i.e. during late MIS 3 and MIS 2. MIS 3 is recorded as a palaeosol complex including two humic A horizons overlying a chromic cambisol associated with burrows of ground squirrels, while MIS 5 corresponds to a reworked rubified chromic cambisol. Overall, this sequence shows similarities with the clastic deposits found in regional cave porches and rock shelters, strongly suggesting that anthropogenic activities did not significantly modify the climate‐driven sedimentary and soil‐forming processes at the Palaeolithic sites.

Last Glacial Maximum active layer thickness in Western Europe, and the issue of ‘tundra gleys’ in loess sequences - Pascal Bertran; Kim H. Stadelmaier; Patrick Ludwig (Journal of Quaternary Science, 2022)
Late Marine Isotope Stage (MIS) 3 and MIS 2 loess–palaeosol sequences in Western Europe comprise alternating loess layer and 3‐ to 30‐cm‐thick bleached soil horizons with Fe–Mn oxide precipitations, which are usually interpreted as waterlogged active layers and referred to as ‘tundra gleys’. Active layer thickness data derived from a regional climate model simulation and the fossils (shells, earthworm granules) found in ‘tundra gleys’ argue against such an assumption. Most of these horizons better correspond to Fe‐depleted, slightly humic topsoil horizons or subsurface eluvial horizons and should be referred to as (incipient) Ag or Eg horizons. They formed during climate ameliorations associated with vegetation (cryptogams, herbs) development, possibly limited by long‐lasting snow cover. Strong mixing usually occurred in these horizons due to the activity of anecic earthworms and frost activity.

Paleoclimate variations and impact on groundwater recharge in multi-layer aquifer systems using a multi-tracer approach (northern Aquitaine basin, France) - Marc Saltel; Romain Rebeix; Bertrand Thomas; Michel Franceschi; Bernard Lavielle; Pascal Bertran (Hydrogeology Journal, 2019)

A map of Pleistocene aeolian deposits in Western Europe, with special emphasis on France - Pascal Bertran; Morgane Liard; Luca Sitzia; Hélène Tissoux (Journal of Quaternary Science, 2016)
The Land Use and Cover Area frame Statistical survey (LUCAS) database on topsoil properties in Europe was used to map aeolian deposits. The points which satisfy the grain‐size criteria of coversands, loess and transitional facies were extracted from the rasters of predicted soil texture established by kriging of the LUCAS data by Ballabio et al . ( ). A comparison with already available maps, derived from a conventional field approach, shows a good fit in most of the tested areas. The new map, however, suggests a greater extension of loess, which seems related to the inclusion of thin loess covers, usually omitted by conventional mapping, and the presence of previously unmapped areas due to lack of survey or misinterpretation. The main source of aeolian particles corresponds to glacio‐fluvial sediments at the margin of the Scandinavian and Alpine ice sheets. Coversands and loess form a broad band across northern Europe, and in the Rhône, Rhine and Danube valleys. Large areas on the outskirts of these deposits also received a significant loess contribution, which has been reworked in slope deposits. Conversely, southern Europe is characterized by much less loess accumulation. The Atlantic coast has transgressive dune fields that penetrate inland to varying degrees.

Architecture of the lower terraces and evolution of the Dordogne River at Bergerac (south‐west France) during the last glacial–interglacial cycle - PASCAL BERTRAN; MARINE FROUIN; NORBERT MERCIER; FABIEN NAESSENS; FRÉDÉRIC PRODEO; ALAIN QUEFFELEC; COLETTE SIRIEIX; LUCA SITZIA (Journal of Quaternary Science, 2013)
The lower terraces of the Dordogne River at Bergerac (south‐west France) were studied in detail using cores, trenches, ground penetrating radar profiles, and 14 C, optically stimulated luminescence and infrared stimulated luminescence dating. This study shows that the lowest terrace (Fx) is made up of two major lithostratigraphic units: (i) dominantly horizontal gravel strata interpreted as compound bar deposits in a braided river, which pre‐date 18–17 ka, and (ii) thick lateral accretion gravel units (point bars) formed in an anabranching river during the Late Pleniglacial and Lateglacial. Most of the anabranching channels were abandoned at ca. 11–10 ka following shrinkage of the river bed into a single meandering channel and were partially filled by gyttjas during the Boreal chronozone. Finally, the channels were plugged by overbank fines until about 5 ka. Floods seldom reached the Fx terrace during the late Holocene and accretion became negligible. The main phase of bedrock incision spanned the Holocene, whereas the period of channel adjustment to change in river regime during late Marine Isotope Stage (MIS) 2 only led to a redistribution of the Pleniglacial gravels. The higher terrace (Fw3) formed before the Eemian and was covered by colluvial fans, mainly during MIS 2 and 3. Copyright © 2013 John Wiley & Sons, Ltd.

Inland aeolian deposits of south‐west France: facies, stratigraphy and chronology - Pascal Bertran; Mark D. Bateman; Marion Hernandez; Norbert Mercier; Dominique Millet; Luca Sitzia; Jean‐Pierre Tastet (Journal of Quaternary Science, 2011)
Archaeological investigations undertaken along a proposed highway together with the compilation of available geological and pedological data made it possible to give a first overview of the distribution of Pleistocene aeolian deposits in south‐west France. A chronological framework for deposition has been obtained using both radiocarbon ( n = 24) and luminescence ( n = 26) dating. It shows that aeolian transport was very active during the Late Pleniglacial, between 15 and ∼23 ka, leading to sand emplacement over a 13 000‐m 2 area at the centre of the basin. The Pleniglacial coversands are typified by extensive fields of small transverse to barchanoid ridges giving way to sandsheets to the east. Subsequent aeolian phases, at ca. 12 ka (Younger Dryas) and 0.8–0.2 ka (Little Ice Age), correspond to the formation of more localized and higher, mainly parabolic dunes. At the southern and eastern margins of the coversand area, aeolian dust accumulated to form loess deposits, the thickness of which reaches ∼3 m on the plateaus. Luminescence dates together with interglacial‐ranking palaeoluvisols between the loess units clearly indicate that these accumulations built up during the last two glacial–interglacial cycles. The chronology of sand and loess deposition thus appears to be consistent with that already documented for northern Europe. This suggests that it was driven by global climate changes in the northern hemisphere. The relatively thin aeolian deposits (and particularly loess) in south‐west France is thought to reflect both a supply‐limited system and a moister climate than in more northern and continental regions. Copyright © 2011 John Wiley & Sons, Ltd.

Coversand and Pleistocene palaeosols in the Landes region, southwestern France - Pascal Bertran; Giselle Allenet; Thierry Gé; Filipa Naughton; Philippe Poirier; Maria F. Sanchez Goñi (Journal of Quaternary Science, 2009)
New sections in the coversand of the Landes region, southwestern France, show at least two main depositional phases corresponding to the Upper Pleniglacial and the Lateglacial, which are separated by palaeosols. The lower palaeosol, a gleyic to histic cryosol overlying a net of sand wedges and dated to ca. 23 14 C ka BP, testifies to a short occurrence of permafrost. Impeded drainage due to the frozen subsoil is assumed to be the main factor involved in lowered aeolian transport and soil formation. Pollen analysis indicates a shrub tundra‐type environment. The overlying coversand unit is associated with small transverse ridges or sheet‐like deposits, and corresponds to the maximal extension of the sands, Upper Pleniglacial in age. An incipient podzol developed on the dunes under a boreal pine forest, and has been dated to 11.5–12 14 C ka BP, i.e. to the Allerød period. This has been buried by the second coversand unit during the Younger Dryas, typified by abundant denivation features and root imprints. Although preliminary, the chronology of sand deposition in the Landes region appears thus to be roughly similar to that found for the other European coversands, showing that all were the result of similar western European climatic changes, i.e. repeated episodes of increasing aridity related to the Upper Pleniglacial and the Younger Dryas episode. Copyright © 2008 John Wiley & Sons, Ltd.